Studi kualitas pewarnaan alami kulit bawang merah pada kain batik - Laksana, Haniko Candra; Widadi, Zahir; Sasongko, Aditya Dimas Wahyu (Fakultas Teknik Universitas Pekalongan bekerjasama dengan Asosiasi Perajin dan Pengusaha Batik (APPBI), 2024)
Shallots are a plant that is often used in human life. The waste product from shallots that can be used is shallot skins, where the shallot skins are usually just thrown away. This research uses a study of the quality of natural coloring of shallot skin on batik cloth. This research aims to determine the quality of the natural color of shallot skin on batik cloth. The process of researching the quality of shallot skin dye is that a cloth sample is attached to wax and then colored using shallot skin dye which has been extracted and fixed using an alum fixator. After that, the fabric sample is subjected to a night release process. Test samples in the laboratory through color fastness tests to wax release, color fastness tests to washing, color fastness tests to rubbing and color fastness tests to sunlight. Evaluate the resulting values ​​using gray scale and staining scale tools. The results of color fastness to waxing, washing, rubbing and sunlight are very low. This is because the anthocyanin and flaponoid compounds carried by shallot skin tend to be few or the coloring substances produced are very light.